Pengaruh Dana Desa terhadap Pertumbuhan Ekonomi dan Kesejahteraan Masyarakat Desa - Baidlowi, Imam (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the impact of Village Funds on economic growth and the welfare of rural communities. Village Funds are a government fiscal policy instrument expected to stimulate village economic development and improve community welfare. This study uses a quantitative approach with an associative-causal research method. Secondary data were obtained from the Central Statistics Agency (BPS), village government reports, and other official sources. The classical assumptions of data normality, heteroscedasticity, multicollinearity, and autocorrelation were tested. Linear regression analysis was used to analyze the impact of Village Funds on village economic growth and community welfare. The coefficient of determination analysis indicates that community welfare is 48.9% determined by village funds and village economic growth. The F-test concluded that the model formulated in the regression equation is appropriate. The results indicate that Village Funds have a positive and significant impact on village economic growth. Furthermore, Village Funds have also been shown to have a positive and significant impact on village community welfare. These findings suggest that increasing Village Fund allocations can stimulate village economic activity through infrastructure development and community empowerment, ultimately increasing income and the quality of life of rural communities. Equitable distribution of the benefits of economic growth and improved quality of public services also improve welfare. This study implies that effective and targeted management of Village Funds needs to be continuously improved to optimize its benefits for economic growth and community welfare.